Potensi Pasta Gigi Minyak Atsiri Temulawak (Curcuma xanthorriza Roxb) dalam Menghambat Pembentukan Plak dan Gingivitis pada Tikus yang Diinduksi Phorpyromonas gingivalis - Yumnaina Nurhadi; Pujiana Endah Lestari; Peni Pujiastuti (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2022)
Gingivitis is an inflammatory disease in gingiva without any loss of attachment caused by plaque. Gingivitis is reversible, if not treated it can develop into periodontitis. Gingivitis-causing bacteria include Phorpyromonas gingivalis, acting as secondary bacteria in plaque formation at the secondary colonization stage by attaching themselves to monolayers that have been formed by primary bacteria. Herbal use in Indonesia is still a trend until now with the slogan back to nature, one of the easy to find and useful is essential oil from curcuma rhizomes containing xanthorrizol and curcumin. They are antibacterial that can inhibit the formation of plaques that cause gingivitis. The purpose was to analyze the potential of curcuma essential oil toothpaste in inhibiting the formation of plaque and gingivitis. 27 wistar mice were divided into 9 groups, namely negative control group, positive control, treatment applied curcuma essential oil toothpaste concentration of 0.5%, 1%, 2%, 4%, 8%, 16% and 32%. Each mouse induced P. gingivalis 0.02 ml on molar sulkus one and two, 24 hours later performed tooth brushing with toothpaste according to the group, the next 24 hours were observed in day 3, 5 and 7 using plaque index according to Park and Katz and gingiva index according to Lee. Treatment and observation are carried out 3 repetitions. The results of the plaque index score and gingiva index in the treatment group were fewer than the negative controls. Curcuma essential oil toothpaste can inhibit the formation of plaque and gingivitis by decreasing the plaque index and gingiva index in P. gingivalis- induced wistar mice.